Prioritization mechanisms in working memory modulate perceptual interference - Jung, Koeun; Han, Suk Won (Environment and Social Psychology, 2025)
Working memory provides temporary storage of information needed for immediate responses. Within this system, individuals can also prioritize certain items, enhancing the representation of those items. An ongoing debate concerns whether prioritized information is protected from or vulnerable to external stimuli remains debated. The present study examined how prioritization mechanisms of working memory interact with perceptual interference from external stimuli. Participants performed a working memory task in which item priority was manipulated using either value-based cues or spatial cues, presented either before encoding or during maintenance. Following the memory display, a to-be-ignored suffix item (a geometric shape) was either presented or omitted. In this way, we examined whether the extent of suffix interference would vary depending on the type and timing of prioritization. The results showed that the interference effect of suffix items on prioritized information is not consistent but is observed only under specific conditions. In particular, prioritized items were more susceptible to suffix interference only when high value was assigned before encoding. By contrast, when value-based prioritization was applied during maintenance, no such interference was observed. Similarly, spatial cueing-based prioritization protected prioritized items from suffix interference regardless of whether cues were given before encoding or during maintenance. These findings suggest that different forms and timings of prioritization in working memory interact distinctly with perceptual interference from irrelevant stimuli.